Method Development and Validation of a New Stability-indicating Liquid Chromatographic Method for the Quantification of Ketorolac Tromethamine (A Nonsteroidal Anti-inflammatory Drug) - Pudi, Rajesh (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: A new liquid chromatographic method was established for the determination of ketorolac tromethamine (KTM). KTM is a nonsteroidal anti-inflammatory drug. Materials and Methods: Shimadzu Model CBM-20A/20 Alite with C8 Phenomex column (250 mm Ã— 4.6 mm i.d., 5 Î¼m particle size) was used for the chromatographic study. A mixture of 0.1 M ammonium formate and methanol was chosen as mobile phase with flow rate of 0.8 mL/min (UV detection at 241 nm). KTM was subjected to acidic, alkaline, oxidation, and thermal stress degradations. Results and Discussion: The method was validated as per ICH guidelines, and the regression equation was found to be y = 68207x +57590 (RÂ² = 0.9997). The limit of quantification and limit of detection were found to be 0.7834 and 0.2571 Î¼g/mL, respectively. KTM is found to be highly resistant toward all degradations. Conclusions: The method was reported to be robust and specific and can be applied for the assay of pharmaceutical formulations.